The Effect Of Nanocellulose On PVDFCarbon Black In The Fabrication Of Conductive Thin Films For Electrochemical Applications - Husin, Iqbal Aiman Kamal (Universiti Sains Malaysia, 2022)
Flexible and freestanding cellulose-based thin films have been prepared via two methods for use in various electrochemical applications. The first method involving the blending of nanocellulose with PVDF and the added carbon black has shown satisfactory electrochemical behaviour at a very low scan rate of 0.005 V/s or 0.5 mV/s. Low content of CNF of 10 wt% is adequate for generating flexible features while retaining the conductivity of the film, whereas higher CNF content increases film resistance. The coating of CNF film in PVDF/CB conductive ink shows a successful CV test over a wide range of scan rates. The presence of LiCl during the preparation of CNF film has significantly increased the electrochemical behaviour of the measured film. Even though carbon loading should increase conductivity, adhesion on the coated substrate is most dependent on the PVDF binder. The nanocellulose film with 20 wt% of LiCl and a 5 to 5 ratio of PVDF/CB conductive inks proves to have good electrochemical performance based on the current response and the area of the CV obtained. The highest current response was recorded at the maximum applied potential of 0.6 V, whereas the lowest was at -0.3 V. The bending reveals the increment in resistivity, thus indicating a reduction in conductivity, though it is able to be used again after being tested with CV.